Higher live birth and lower pregnancy loss rates in natural compared with artificial cycle protocols for endometrial preparation of frozen blastocyst transfer: Višja stopnja živorojenosti in nižja stopnja spontanih splavov v protokolih z naravnim ciklusom za pripravo endometrija za prenos zamrznjenih blastocist v primerjavi s protokoli z umetnim ciklusom - Reljič, Milan; Mlakar, Lea; Hadžimehmedović, Azra; Kovač, Vilma (Acta Medico-Biotechnica, 2021)
Purpose: The aim of this study was to compare the reproductive outcomes and live birth rates of natural cycle (NC) and artificial cycle (AC) protocols for endometrial preparation of frozen– thawed embryo transfer (FET).Methods: A total of 1317 NC and 528 AC protocols for endometrial preparation of FET performed during a 3-year period at a tertiary in vitro fertilisation (IVF) clinic were analysed. The clinical spontaneous abortion, pregnancy, and live birth rates were compared. Logistic regression models were constructed to identify the factors that are significantly associated with the live birth and clinical spontaneous abortion rates.Results: A significantly lower clinical spontaneous abortion rate (13.68 % vs. 27.32 %; p < 0.001) and a comparable pregnancy and a significantly higher live birth rate (32.82 % vs. 26.70 %; p < 0.01) were associated with the NC compared to the AC protocol. Independent predictors for live birth were maternal age (odds ratio (OR), 0.94; 95% confidence interval (CI), 0.91–0.98), transfer of morphologically- optimal blastocysts (OR, 1.72; 95% CI, 1.28–2.31), and the method used to prepare the endometrium (OR, 0.63; 95% CI, 0.45–0.88). Independent predictors of clinical spontaneous abortion were the method used to prepare the endometrium (OR, 2.26; 95% CI, 1.39–3.68) and maternal age at the time of FET (OR, 1.07; 95% CI, 1.02–1.13).Conclusions: A better reproductive outcome was observed with the NC protocol; specifically, the clinical spontaneous abortion rate was significantly lower and the live birth rate was significantly higher compared with the AC protocol. Based on better cycle outcomes, patient convenience, and low cost, we suggest using the NC protocol as the first option for FET in patients with regular menses.
Keywords: frozen blastocyst transfer; natural cycle; artificial cycle